DIFFERENCES IN THE RESULTS OF ABO BLOOD TYPE EXAMINATION USING ANTISERA REAGENTS AND SERUM SLIDE METHOD - Emma Ismawatie; Resi Tondho Jimat; Arum Kusuma Putri; Adi Kurniawan (PT. Jurnal Center Indonesia Publisher, 2026)
Blood group examination is a blood grouping system based on the type of antigen. Examination of blood groups with antisera reagents, namely examination of blood groups with antisera reagents obtained from in vitro supernatant cultures derived from mouse cell immunoglobulin hybridization. Examination of blood type with serum is an examination that uses blood type A as anti-B, blood type B as anti-A, and blood type O as anti-AB. The purpose of this study was to determine the profile of the ABO system blood group examination using antisera reagents and serum slide method. The research method used was descriptive with samples of the ABO system blood group using antisera and serum reagents for 30 respondents using probability sampling technique. The materials used are human blood groups A, B, AB and O and anti-A, anti-B, anti-AB reagents. Data analysis was descriptive in the form of a profile table of the results of the ABO system blood group examination using antisera and serum reagents. The results of the study revealed that the results of blood group A were 7 (23%), blood group B were 7 (23%), blood group AB were 8 (27%), and blood group O were 8 (27%). The results obtained showed that the antisera and serum reagents had differences in the blood group examination results, namely the grade of agglutination produced by the serum was different from that of the antisera. It can be concluded that the results of blood grouping with antisera and serum reagents can be used for blood group examination. However, compared to antisera reagents, the results are better using antisera reagents compared to serum.